2004
DOI: 10.1103/physrevlett.93.145302
|View full text |Cite
|
Sign up to set email alerts
|

A1andA2Transitions in SuperfluidHe

Abstract: Superfluid 3He in high porosity aerogel is the system in which the effects of static impurities on a p-wave superfluid can be investigated in a systematic manner. We performed shear acoustic impedance measurements on this system (98% porosity aerogel) in the presence of magnetic fields up to 15 T at the sample pressures of 28.4 and 33.5 bars. We observed the splitting of the superfluid transition into two transitions in high fields in both bulk and liquid in aerogel. The field dependence of the splitting in ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 23 publications
3
17
0
Order By: Relevance
“…But higher field experiments are required, as well as measurements with 4 He preplating, to reach a firm conclusion. In this spirit Choi et al 72) extended the field range of Gervais et al 21) to H ¼ 14 T using the same aerogel sample, and their results are reproduced in Fig. 13.…”
Section: )mentioning
confidence: 49%
See 2 more Smart Citations
“…But higher field experiments are required, as well as measurements with 4 He preplating, to reach a firm conclusion. In this spirit Choi et al 72) extended the field range of Gervais et al 21) to H ¼ 14 T using the same aerogel sample, and their results are reproduced in Fig. 13.…”
Section: )mentioning
confidence: 49%
“…13. Splitting of the A 1 À A 2 transition at high magnetic field for superfluid 3 He in a 98% aerogel (solid circles and crosses) and in pure 3 He (open circles) at two pressures by Choi et al 72) at the University of Florida. The linear slopes with magnetic field are rather similar for pure and aerogel superfluids.…”
Section: Specific Heat Thermal Conductivity Gaplessnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Both theoretical 53,54) and experimental studies have been carried out on various aerogel-3 He systems. Zero sound propagation was measured in a 98% porosity Aerogel in magnetic field up to 15 T. 55) The measurements showed that indeed the superfluid transition split into two as evidence for the appearance of A 1 phase in liquid 3 He confined in the Aerogel. The splittings were similar to those in bulk and indicated that the impuritydoped superfluid 3 He behaved as a p-wave superfluid.…”
Section: Phase Diagrammentioning
confidence: 99%
“…The phase diagram of 3 He/aerogel ͑with mostly 98% porosity͒ has been studied using a variety of techniques. [5][6][7][8][9][10][11] To date, three distinct superfluid phases have been observed in 3 He/aerogel; these are called the A, B, and A 1 phases 10 as in the bulk, although the detailed structures of the order parameters ͑especially the orbital component͒ have not been identified. Early studies using NMR 6 and torsional oscillator 5 measurements on 3 He in 98% porosity aerogel found substantial depression in the superfluid transition and a theoretical account based on the homogeneous isotropic scattering model ͑HISM͒ was provided.…”
mentioning
confidence: 99%